Znaczenie metafor pojęciowych na przykładzie prawa autorskiego - Zalewska, Monika (Filozofia Publiczna i Edukacja Demokratyczna, 2016)
The problematic gap between legal and social norms exists in copyright law. The consequences of this gap are severe and include: not following copyright rules, and a big conflict between artists and recipients of a culture. In this context, copyright piracy is prevalent in Poland and legal tools aimed to protect interests of artists have failed. Copyright law might have been in sync with analogue era, but not to digital world. Identification of roots of the discrepancy between social expectations and legally binding rules might be the first step toward rectifying of situation. This article demonstrates the conceptual metaphors as a possible reason for malfunctioning the copyright law. Some metaphors treat intangible objects as tangible ones (intellectual or artistic work) and might pose difficulties mentioned above. Additionally, Larsson defined a group of metaphors in legal system. Bound with them are metaphors outside of law. For example, if law treats intellectual property as tangible property, than metaphors outside the copyright legal system, such as piracy apply. Polish copyright law in the context of Lakoff – Johnson theory of metaphors is a framework of the study.